Inflation in Inhomogeneous Spacetimes: Bubble Evolution - Teppa Pannia, Florencia Anabella (2015)
The evolution of a vacuum bubble embedded in an inhomogeneous spacetime is elevant for the modelling of inflation in the presence of inhomogeneities. We developed a numerical scheme based on Israel´s matching conditions to solve the evolution of the bubble for spherically symmetric inhomogeneous backgrounds. Particular attention is paid to spacetimes with perfect fluid with non-zero pressure as a source, which are described by Lemaître solution of Einstein´s equations. As a previous step that serves as a check of the numerical scheme, we present here the case of a bubble evolving in a FLRW metric with radiation as a source.